2017
DOI: 10.1080/14623528.2017.1393942
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of Mass Murder: A Case for Understanding the Indonesian Killings as Genocide

Abstract: This article presents an overview of new evidence recovered from the former Indonesian Intelligence Agency's archives in Banda Aceh that is able to prove, for the first time, military agency behind the 1965-66 killings in Indonesia. The military leadership, these documents show, initiated and implemented the killings as part of a coordinated national campaign. This campaign was described by the military leadership as an "annihilation operation" and was implemented with the stated intention to "annihilate to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…3) In 1965, Indonesia faced critical times as communist party did maneuver to kill some Indonesia generals. This was followed by a tragedy of large-scale killings and civil unrest which occurred over several months, targeting communist sympathizers, ethnic Chinese and alleged leftists, often at the instigation of the armed forces and government (Melvin, 2017). Hermeneutically, as the president, and as the founding father, Soekarno has felt crucial situation before the tragedy happened.…”
Section: Methodsmentioning
confidence: 99%
“…3) In 1965, Indonesia faced critical times as communist party did maneuver to kill some Indonesia generals. This was followed by a tragedy of large-scale killings and civil unrest which occurred over several months, targeting communist sympathizers, ethnic Chinese and alleged leftists, often at the instigation of the armed forces and government (Melvin, 2017). Hermeneutically, as the president, and as the founding father, Soekarno has felt crucial situation before the tragedy happened.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore the nation has been established and preserved. Unfortunately, facts have shown that nowadays, some Indonesian people are trying to destroy the ideologies and change it with ISIS and Khilafah Ideology (Mohamed, 2010;Liow, 2014;Jones, 2015;Galamas, 2015).…”
Section: Why Indonesia?mentioning
confidence: 99%
“…In 1965, Indonesia faced critical times as the communist party maneuvered to kill a number of Indonesian generals. This was followed by the tragedy of large-scale killings and civil unrest which occurred over several months, targeting communist sympathizers, ethnic Chinese and alleged leftists, often at the instigation of the armed forces and government (Melvin, 2017). Hermeneutically, as the president, with evidence of foresight, Soekarno appeared to feel and sense the crisis before the tragedy happened.…”
Section: Diagrammentioning
confidence: 99%